EFFICIENCY OF BLANKETS WITH ACTIVE SELF-HEATING TECHNOLOGY IN THE POST-SURGERY PERIOD - S. P. Kozlov; V. M. Kraynik (Вестник анестезиологии и реаниматологии)
The trail was conducted with the purpose to compare two heating devices in the groups of patients who had surgery due to varicose veins of the lower extremities with spinal anesthesia with intravenous sedation in the  intra- and post-operative periods. It was found out that warming with the help of blankets with active self-heating technology is more efficient for prevention and treatment of intra-operative hypothermia compared to resistive mattresses. The article includes discussion of mechanisms of intra-operative hypothermia development, its negative eﬀects and measures for its prevention and treatment. Recommendations on the use of this equipment are given.